2011
DOI: 10.1007/s00404-011-1988-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pelvic radiotherapy on female sexuality

Abstract: Purpose To assess physical and psychological morbidity, sexual functioning and social and relationship satisfaction among women treated with pelvic radiotherapy. Methods Observational (case-control) study of 199 women: 98 submitted to pelvic radiotherapy for the treatment of uterine, rectal or anal cancers and 101 without a personal history of cancer and similar socio-demographic variables. These completed a socio-demographic and Results Women submitted to pelvic irradiation reported a higher rate of adverse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
1
22
0
3
Order By: Relevance
“…Their own FSFI total and domain scores were significantly lower than those in the study group, with the exception of satisfaction, and desire was the most compromised. 18 In this study, 52.0% of patients in the RT group were older than 60 years. Frumovitz et al 17 described that using the FSFI, all domains of sexual function except desire were significantly lower in patients treated with RT.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Their own FSFI total and domain scores were significantly lower than those in the study group, with the exception of satisfaction, and desire was the most compromised. 18 In this study, 52.0% of patients in the RT group were older than 60 years. Frumovitz et al 17 described that using the FSFI, all domains of sexual function except desire were significantly lower in patients treated with RT.…”
Section: Discussionmentioning
confidence: 57%
“…With regard to each domain score of FSFI, Rodrigues et al 18 reported on 98 women after pelvic RT, of which 82 had cervical or uterine cancer, and who were compared with women undergoing routine cervical cancer screening. Their own FSFI total and domain scores were significantly lower than those in the study group, with the exception of satisfaction, and desire was the most compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Varios estudios describió a las pacientes femeninas que experimentaron cirugía pélvica sentía que su vagina era inelástica y demasiado corta durante las relaciones sexuales (Bergmark, Avall-Lundqvist, Dickman, Henningsohn, y Steineck, 1999;Platell, Thompson, y Makin, 2004). La radioterapia también puede comprometer la función sexual en las pacientes con cáncer rectal (Rodrigues et al, 2012). Un estudio noruego comparó la función sexual en las mujeres después de radioterapia para el cáncer rectal.…”
Section: Estudios De Calidad De Vida Y Factores Psicosociales En La Cunclassified
“…12,13 Sexual dysfunction after cancer treatment is common in female survivors. 4,14-20 A survey of 221 survivors of vaginal and cervical cancer found that the prevalence of sexual problems was significantly higher among survivors than among age- and race-matched controls from the National Health and Social Life Survey (mean number of problems 2.6 vs 1.1; P <.001). 18 A survey of survivors of ovarian germ cell tumors and age-, race-, and education-matched controls found that survivors reported a significant decrease in sexual pleasure.…”
Section: Female Aspects Of Sexual Dysfunctionmentioning
confidence: 99%